2013
DOI: 10.1007/s12975-013-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated Potassium Channels at the Crossroads of Neuronal Function, Ischemic Tolerance, and Neurodegeneration

Abstract: Voltage-gated potassium (Kv) channels are widely expressed in the central and peripheral nervous system, and are crucial mediators of neuronal excitability. Importantly, these channels also actively participate in cellular and molecular signaling pathways that regulate the life and death of neurons. Injury-mediated increased K+ efflux through Kv2.1 channels promotes neuronal apoptosis, contributing to widespread neuronal loss in neurodegenerative disorders such as Alzheimer’s disease and stroke. In contrast, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 327 publications
(455 reference statements)
2
88
0
Order By: Relevance
“…These channels are present throughout the nervous system (Brown and Passmore 2009;Delmas and Brown 2005;Jentsch 2000), and their dysfunction is involved in several disease states (Cooper and Jan 2003;Li et al 2013;Passmore et al 2003;Shah and Aizenman 2014;Zheng et al 2012). Using a well-established theoretical framework to study correlation transfer in spiking neurons (de la Rocha et al 2007), we showed that the recruitment of Kv7 conductances provides an input-driven negative feedback that cancels correlating inputs and reduces the covariability of pairwise spiking activity in model neurons.…”
Section: Discussionmentioning
confidence: 84%
“…These channels are present throughout the nervous system (Brown and Passmore 2009;Delmas and Brown 2005;Jentsch 2000), and their dysfunction is involved in several disease states (Cooper and Jan 2003;Li et al 2013;Passmore et al 2003;Shah and Aizenman 2014;Zheng et al 2012). Using a well-established theoretical framework to study correlation transfer in spiking neurons (de la Rocha et al 2007), we showed that the recruitment of Kv7 conductances provides an input-driven negative feedback that cancels correlating inputs and reduces the covariability of pairwise spiking activity in model neurons.…”
Section: Discussionmentioning
confidence: 84%
“…Zinc also contributes to neuronal death in hypoxic-ischemic injury (34,35,(47)(48)(49) by interfering with mitochondrial and metabolic functions (50,51), altering ion fluxes (52), and other mechanisms (53). Abnormalities in zinc homeostasis may be important in chronic neurodegenerative diseases, such as Alzheimer's (54) and amyotrophic lateral sclerosis (55)(56)(57), and have been shown to play a key role in oxidative stress-induced death in neurons and oligodendrocytes (58,59).…”
Section: Significancementioning
confidence: 99%
“…Finally, increased K þ conductance and the gradual accumulation of extracellular K þ that occur during ischemia generally contribute to membrane hyperpolarization and repolarization thereby depressing neuronal excitability. 25 This ionic imbalance may effectively inhibit SD elicitation as well.…”
Section: Electric Threshold To Elicit Spreading Depolarizationmentioning
confidence: 99%